THE DIGITAL ECONOMY PART OF THE INTERNATIONALIZATION OF THE LABOR MARKET. THE CASE OF ALBANIA - Matilda Gjoni (Meta); Endrit Elezi (Agora International Journal of Economical Sciences, 2023)
This study aims to analyze the impact of the digital economy on strengthening the labor market and its growth in Albania. In this analysis, we focus on the growth of the Information and Communication Technology (ICT) sector as a result of technological advancements and innovation in the country. Using official data from Albanian state sources, we identify the changes and challenges of the labor market in this context of digital transformation. Also, we research the policies and strategies undertaken by state institutions to improve the adaptation of the workforce to the demands of the digital economy sector. Through our analysis, we assess the role of training and skills development as well as their impact on increasing employment and innovation in Albania. Based on the results of the study, we conclude with concrete recommendations to improve existing strategies and policies in accordance with the needs of the digital economy sector and the workforce in Albania. In conclusion, we examine the future opportunities for the growth of the digital economy and the labor market in the country. The intercommunalization of digitalization is a trend for global economic development, a necessary part of the high-quality development of any business. The internationalization of digitization suggests that the principles of sustainability and digitization can and should be combined with each other to ensure business longevity. Artificial intelligence, quantum computing, brain-computer interface, digital transformation of enterprises, digital technology and digitization are gaining ground in global economic development.